John Dewey and the importance of the "qualitative" for democracy - Pappas, Gregory Fernando (Pontificia Universidad Católica del Perú. Fondo Editorial, 2015)
In spite of the fact that Dewey wrote about the importance of the «qualitative» (i.e. what is non-cognitive, non-linguistic, and has been associate with «feelings»), there are only a few Dewey scholars that have stressed or have continue to reconstruct this aspect of his philosophy1 . This is puzzling, especially when there is a growing body of research in social psychology and the cognitive sciences that supports Dewey’s view of thinking as qualitative (see Green & Haidt, 2002; Haidt, 2001, and Varela, 1999). My concern here, however, is not to ponder critically on the motives why deweyeans have been conservative on this issue, but to provide a positive argument why deweyeans (and pragmatists in general) must, more than ever, embrace and continue to inquiry about the «qualitative» in experience. I will argue that if you care about democracy, and most deweyeans do or are supposed to, then you must inquire about the function of the qualitative in democracy. Dewey argued that democracy was a never ending task. I will suggest some positive and promising tasks for us (deweyeans) as we reconstruct his philosophy for the 21st century. The poor quality of public discourse in America requires us to expand Dewey’s logic to include and elaborate the insights that he left us about the unavoidable role of the qualitative in thinking. There is a need for more interdisciplinary research, an embracing of the «affective revolution» in the sciences, but one that is critical of the dualism of reasoning and sentiment.
Páginas 173-188
Keywords: Democracia; https://purl.org/pe-repo/ocde/ford#6.03.01